The Effect of Different Extraction Temperatures of SARS-COV2 RT-PCR Examination Process On CT Value In Patient Specimens In Labkesda Kabupaten Sukabumi, Indonesia - Fadhilah, Fitri Rahmi; Wahid, Aziz Ansori; Rachman, Mochamad Irwan Fitriana (Asian Journal of Health and Applied Sciences, 2022)
The Severe Acute Respiratory Syndrome Coronavirus-2, or COVID, was announced by WHO on February 11, 2020.  Examination of SARS-CoV2 by RTq-PCR method in Labkesda Kab. Sukabumi is one of the health service support units in the Sukabumi area. The number of PCR examination requests is increasing every day, whereas, at this stage, the temperature increase process should reach the recommended temperature of 90°C, which can take 20-25 minutes. Sometimes ATLM has processed specimens at 60°C - 90°C. Given the required temperature at the time of extraction, which is at a temperature of 90 degrees, here the researchers wanted to prove whether below 90 degrees had an effect on the virus extraction process. This study aims to determine the effect of differences in extraction temperature on the SARS-CoV2 RTq-PCR examination process on CT VALUE on patient specimens. The variable in this study was the difference in temperature consisting of 60°C, 80°C, and 90°C. This research used quantitative research methods with case studies. This study is an experimental study to determine the effect of temperature differences on the CT value of the RTq - PCR examination. The population of this study were 30 patients at LABKESDA Kabupaten Sukabumi. This analysis used a one-way ANOVA test analysis with software. IBM SPSS 23.0. It may be concluded that there is no significant difference in the CT Value findings on the SARS-CoV2 RTq-PCR Examination since the study's p-value was 0.758, which is more than 0.05.